2016
DOI: 10.1093/icesjms/fsv271
|View full text |Cite
|
Sign up to set email alerts
|

The migration of fin whales into the southern Chukchi Sea as monitored with passive acoustics

Abstract: Fin whales (Balaenoptera physalus) undergo seasonal migration in the Arctic Sea. Because their migration and distribution is likely affected by changes in global climate, we aimed to examine the migration timing of fin whales, and the relationship with prey availability within the oceanographic environment of the Arctic Sea, using passive and active acoustic monitoring methods. Automatic Underwater Sound Monitoring Systems were deployed in the southern Chukchi Sea from July 2012 to 2014 to determine the acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Nishiwaki 29 was the first to suggest that changes in SST might influence the timing of humpback whale (Megaptera novaeangliae) arrival on their wintering grounds. Visser et al 30 tied the timing of peak baleen whale abundance in the Azores to rising SSTs following the spring bloom, and Tsujii et al 31 found that water temperature was a good predictor of fin whale (Balaenoptera physalus) arrival and departure in the southern Chukchi Sea. Our study demonstrates how oceanographic conditions influence migration timing, but also suggests the use of memory.…”
Section: Resultsmentioning
confidence: 99%
“…Nishiwaki 29 was the first to suggest that changes in SST might influence the timing of humpback whale (Megaptera novaeangliae) arrival on their wintering grounds. Visser et al 30 tied the timing of peak baleen whale abundance in the Azores to rising SSTs following the spring bloom, and Tsujii et al 31 found that water temperature was a good predictor of fin whale (Balaenoptera physalus) arrival and departure in the southern Chukchi Sea. Our study demonstrates how oceanographic conditions influence migration timing, but also suggests the use of memory.…”
Section: Resultsmentioning
confidence: 99%
“…This difference in migration timing between coasts could be due to fin whales leaving Antarctic waters at different times, reflecting variation in the timing of annual sea ice formation in different regions of Antarctica. Fin whales migrate away from polar regions when sea ice increases 22,36,44,46,47 . The origin of the migrating animal could also affect the travel and arrival time of the whales.…”
Section: Discussionmentioning
confidence: 99%
“…, Tsujii et al . ). Corresponding taxonomic names include Megaptera novaeangliae (Borowski 1781), Balaenoptera physalus (Linnaeus 1758), Balaenoptera acutorostrata (LacĂ©pĂšde 1804), and Orcinus orca (Linnaeus 1758), respectively.…”
Section: Available Data: a Timeline Of Pals Deployed At Four Sites Inmentioning
confidence: 97%